Le voci di Tanja. Un tessuto di traduzioni mediterranee (Altre Modernità, 2018)
Tangier is the main city of the Northern Moroccan region. As the only one to benefit from the International Status during the French Protectorate, it has always been influenced by multilingualism: the local diglossia, due to the coexistence of the locale dialect, darija, and Standard Arabic, exists side by side with three local darijas of Amazight, official language from 2011; more, due to the colonial period, the general knowledge of Spanish is linked to the territorial control of Spain on the North of Morocco and to the commercial contacts between the shores while French was imposed as official language in the educational and administrative sphere. The identity of translational city (S. Simon, 2012) still exists and it is today still problematized because of the increasing migration flows directed to the cities and originating both in Europe and in the Moroccan countryside. This phenomenon is the result of the unprecedented economical development of the North, due to the set up of de-localized productive activities in free zones spread over the whole territory. The categories of class and gender determine a relation with the languages beginning from situated subjects and reveal the differential inclusion produced in loco. Starting from some interviews to women working in the de-localized textile factories of Tangier, I propose a socio-linguistics analysis aimed to identify some translation processes among situated female universes.